A Recurrent Platinum Refractory Ovarian Cancer Patient With a Partial Response After RRx-001 Resensitization to Platinum Doublet. (6th March 2018) - Cottrill, Hope; Cason, Stephanie; Caroen, Scott; Oronsky, Bryan; Donaldson, Elvis
This case report describes the clinical course of a heavily pretreated patient enrolled on the Phase II QUADRUPLE THREAT clinical trial (NCT02489903) with recurrent metastatic epithelial ovarian cancer that was previously treated with a platinum doublet and that benefited from another reintroduction of a platinum doublet after a brief priming period with RRx-001. Platinum-taxane combination is the initial treatment of choice in ovarian cancer and the "go-to regimen" for patients with recurrent, platinum-sensitive disease. However, platinum resistance is an inevitable and uniformly fatal development. One of the "Holy Grails" in ovarian cancer, besides early detection, is to reverse this resistance and retreat with a platinum doublet regimen. Because of the correlation between therapeutic resistance and poor clinical outcomes, this case, which potentially demonstrates a new avenue of anticancer development in epithelial ovarian cancer provided it is repeatable with other ovarian patients, was felt to merit a report.